2017
DOI: 10.1093/heapro/dax009
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the health and well-being impacts of social enterprise: a UK-based study

Abstract: SummarySocial enterprises–businesses that work for social benefit rather than for the maximization of financial returns to shareholders or owners–could potentially prove to be an innovative and sustainable way of tackling ‘upstream’ social determinants of health. However, empirical work focusing upon how, and to what extent, social enterprise-led activity may impact upon health and well-being is still relatively scarce. This study examines how social enterprises portray their impact, and how such impacts may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…Public health interventions are inherently complex ( Rychetnik et al , 2002 ; Breuer et al , 2015 ) but can act upon the social determinants of health ( Macaulay et al , 2017 ; Suchowerska et al , 2019 ). Such complexity is a result of (i) the magnitude and the range of interacting components; (ii) the flexibility of the intervention and its fit with the local environment; (iii) behaviours, groups or levels and (iv) their outcomes ( Craig et al , 2008 ; Fletcher et al , 2016 ; Grant and Hood, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public health interventions are inherently complex ( Rychetnik et al , 2002 ; Breuer et al , 2015 ) but can act upon the social determinants of health ( Macaulay et al , 2017 ; Suchowerska et al , 2019 ). Such complexity is a result of (i) the magnitude and the range of interacting components; (ii) the flexibility of the intervention and its fit with the local environment; (iii) behaviours, groups or levels and (iv) their outcomes ( Craig et al , 2008 ; Fletcher et al , 2016 ; Grant and Hood, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such complexity is a result of (i) the magnitude and the range of interacting components; (ii) the flexibility of the intervention and its fit with the local environment; (iii) behaviours, groups or levels and (iv) their outcomes ( Craig et al , 2008 ; Fletcher et al , 2016 ; Grant and Hood, 2017 ). It has been suggested that social enterprises have the potential to be a ‘non-obvious actor’ in the delivery of such complex public health interventions ( Roy et al , 2017 ; Calò et al , 2019 ), even where health is not part of the stated social mission of the organization ( Macaulay et al , 2017 ), however, more empirical evidence is needed to determine this ( Calò et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Debates focus on whether SEs can be an alternative provider of healthcare (Hazenberg and Hall, 2016;Roy et al, 2013), to understanding how SEs affect health outcomes (Farmer et al, 2016;Gordon et al, 2017). Much of the former research stream arises from countries where the public health infrastructure is well developed, such as the United Kingdom (UK) (Macaulay et al, 2018(Macaulay et al, , 2017. The latter stream of research examines the pathways by which SEs can address health and wellbeing (Roy et al, 2013), and the social determinants of health (Macaulay et al, 2017;Whitehead and Popay, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the former research stream arises from countries where the public health infrastructure is well developed, such as the United Kingdom (UK) (Macaulay et al, 2018(Macaulay et al, , 2017. The latter stream of research examines the pathways by which SEs can address health and wellbeing (Roy et al, 2013), and the social determinants of health (Macaulay et al, 2017;Whitehead and Popay, 2010). The potential health effects are varied, with the specific impact seemingly dependent on the type of SE (Macaulay et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation